Prediction of Infiltration and Saturated Hydraulic Conductivity of the Soilsin the Iraqi Central Alluvial Plain Using Remote Sensing Technique. - Abbas, Ayad; Muhaimeed, Ahmed (Iraqi Journal of Science, 2024)
Studies within the last two decades have pointed out the importance of remotesensing techniques to deduct soil properties. These techniques showed promisingresults as a suitable alternative with lowest cost in compare with other methods usedto measure soil characteristics (10). The aim of this study is to test the relationshipbetween landsat (ETM + sensor) data and infiltration rate and saturated hydraulicconductivity of soils with ten different selected soil units. These soils which havevariations in geomorphology and soil characteristics are located at the north of Kutcity (Middle part of Iraq to the left of Tigris river). Statistical Analyses wereperformed and statistical models were built up to predict the two soil characteristicsusing remote sensing techniques. The results showed the statistically significance ofthe relations between the soil water infiltration rate values and the remote sensingdata for the soil surface layer, with determination coefficient (R2) of 0.9 . while thesaturated hydraulic conductivity for the soil layer at depth 25-50 cm, showed weakcorrelation .These results demonstrate the weak relation between ETM + sensordata and soil data with depth